Anomalous left coronary artery from pulmonary artery in an adult - Baroopal, Anil; Mathur, Rohit; Sanghvi, Sanjeev; Mahajan, Swati (International Journal of Research in Medical Sciences, 2019)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital cardiac anomaly that can cause myocardial infarction, heart failure and even death in paediatric patients. Only few untreated patients survive till adulthood. Here we present the case of a 28-year-old lady with exertional dyspnoea and chest pain who was diagnosed to have ALCAPA.